Navigating Teaching Practicum in the Real Classroom: Insights from ESL Teaching Practicum Experiences - FADILLAH, Fadillah; JABU, Baso; MUHALIM, Muhalim (Research and Innovation in Applied Linguistics, 2024)
Teaching practicum is one of the compulsory courses that pre-service ESL teachers have to accomplish prior to the completion of their study. Under the lens of experiential learning theory, this study aims to find out pre-service English teachers’ challenges of teaching practicum and how they overcome them. Interviews were used as instruments in this multiple case study, focusing on three pre-service English teachers who participated in the AJARMI program during the 2022–2023 academic year. The findings of this study were analyzed using thematic analysis. The PSETs faced challenges related to students' behaviour, preparation of instructional materials, and mentoring. They handled them with organizing lessons, acting as an assertive teacher, devising a backup plan, and adapting to the school system. The implications of this study suggest that teacher education programs should provide more comprehensive training on classroom management, instructional material preparation, and effective mentoring strategies to better prepare pre-service teachers for the realities of the classroom.